Utilization of Sculpture as System of Continuity in Contemporary Arab Architecture - Ali, Rasha Abdulkareem (Nahrain University College of Engineering Journal, 2014)
Architecture is considered as a language during the last four decades, contemporary studies had presented this trend through different cognitive approaches which includes both the fields of meaning and semiotic as semantic expressions in all events. In Arab countries, it has emerged in reactions concentrating on imitating the global experiences thus an approach towards reconnecting with tradition and culture occurred to meet the demands of our social human culture. Hence, there was a strong need to verify various methods and strategies to reach this goal. The research problem: is the importance of increasing the knowledge concerning "sculpture" which represents one of the basic approaches in Architectural design and discuss the Propositions that dealt with the relation between sculpture and the conceptual appearance of the Architectural Product "appearance and content", while the research particular problem: is to give a total explanation of utilizing the sculptural approach as an adjective to the Architectural product and its role in confirming the characteristics of a building in a way that shapes its form and materials in Architecture in general and in Contemporary Arab Architecture in particular. Thus, the objective of this paper: is to establish an integrated framework consists of four basic terms: (Nature of sculpture, sculpture utilization, sculpture characteristics and sculpture aims). Therefore the research hypotheses was specified to study the possibilities of utilization of sculpture in architecture firstly, then applying one of the main terms (sculpture creation utilization) trend through Contemporary Arab Architecture secondly, concluding the forms of sculpture thirdly. Finally, conclusions have declared that the Architects tend to use Sculpture in their contemporary designs by finding their own methods and strategies to utilize sculpture in Contemporary Arab Architecture.